Digital-Based Scientific Writing Training for Students of the Annuqayah Alumni Association (IAA) Bangkalan Branch - Fiyan Ilmah Faqih; Rahayu, Sri; Bohri Rahman (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The Annuqayah Alumni Association (IAA) Bangkalan Branch is an alumni association of students from the Annuqayah Islamic Boarding School located in Guluk-Guluk, Sumenep Regency. In general, the members of the Annuqayah Alumni Association (IAA) Bangkalan Branch are students currently pursuing their education in Bangkalan Regency, including at the University of Trunojoyo Madura (UTM), STKIP PGRI Bangkalan, and STIKES Ngudia Husada Bangkalan. Members of the Annuqayah Alumni Association (IAA) Bangkalan Branch require scientific writing training to support their academic careers, particularly in writing papers, proposals, laboratory reports, and scientific articles, which are common assignments in nearly all courses.This community service activity is conducted using a needs analysis method, lectures, and discussions, the application of an e-book using the Heyzine app, mentoring and providing facilities such as free access to Turnitin account checks, guidance and consultation sessions, as well as drawing conclusions and evaluations. The results of this community service activity (PkM) show an improvement in the understanding of IAA students regarding the proper methods of scientific writing, as measured by the pre-test and post-test. The pre-test results showed that 55% of students were unable to follow the correct scientific writing procedures, while the post-test results showed a reduction, with only about 14% still unable to do so.